Asymptotic behaviour of transition probability of uniform Markovian process with the finite number of states in the scheme of series - Kinash , О. M.; Кинаш , О. М. (Institute of Mathematics, NAS of Ukraine, 1992)
The asymptotic behavior of the transition probabilities Pij (n)(t/ɛn) for a homogeneous stochastically continuous Markov process with a finite set of states E where E can be represented in the form виде E = E0UE1U…UEr, E0 is the set of unessential states, Ek, k=1, ..., r are ergodic classes.